The influence of trust on internet banking acceptance - Md. Nor, Khalil; Pearson, J. Michael (2007)

(untitled)
The theory of diffusion of innovation (IDT) has been widely used to examine factors that influence an individual to adopt an innovation or a new technology. In online environment, trust has been suggested to play an important role in influencing one’s acceptance of an innovation. The purpose of this study is to test empirically the influence of trust together with some of the attributes of IDT on Internet banking acceptance. We surveyed 1164 business students and MBAs in four public universities in Malaysia. A structural equation modeling was employed to analyze the data. The results show that trust, relative advantage, and trialability, have a significant effect on attitude toward using Internet banking. Consequently, attitude significantly affects the intention to use the technology.